Review: Analysis of Ternary Multiplier using CNTFET - Nagrale V.P.; Patole S.P.; Kumre L.; Verma S.; Kumar A.; Patidar D. (My University, 2025)
During the fullerene property in 1985, carbon nanotube in 1991 and Graphene in 2004, the carbon based nanomaterials have an enormous application in industrial sector. Fullerene is a type of carbon allotrope that are made up of carbon atoms that are linked together to form a closed or partially closed mesh. Carbon Nano Tube is an emerging technology achieving attention in recent times because of their properties like strength, flexibility, conductivity etc. The application of Carbon nanotube including in Engineering, Agriculture and in Medical fields. This review describes an Analysis of Ternary Multiplier using CNTFET which is far better than traditional FET. © 2024 IEEE.